Secondary effects of an opioid-focused academic detailing program on non-opioid controlled substance prescribing in primary care. Issue 4 (October 2021) - Saffore, Christopher D.; Pickard, A. Simon; Crawford, Stephanie Y.; Fischer, Michael A.; Sharp, Lisa K.; Pointer, Sarah; Lee, Todd A.
Background: Educational outreach programs that focus on safe opioid prescribing and awareness of state prescription monitoring programs may modify clinicians' prescribing behavior. The objective of this study was to evaluate the secondary effects of an opioid-focused academic detailing (AD) program on non-opioid controlled substance prescribing in primary care. Methods: A quasi-experimental pre-post study of primary care clinicians exposed and unexposed to the AD program was conducted using data from the Illinois Prescription Monitoring Program from December 2017 to February 2019. Outcomes were mean monthly prescriptions for benzodiazepines (BZD), non-BZD sedative-hypnotics, and carisoprodol, per clinician. A difference-in-differences (DID) approach utilizing repeated-measures mixed-effects linear regression models was used to compare changes in outcomes six-months before and after the program. Results: Mean monthly BZD prescriptions declined in both groups of clinicians (AD-exposed n  = 151; controls n  = 399) after implementation of the AD program. Although the mean monthly number of BZD prescriptions decreased in both groups after the AD program, BZD prescribing in the AD-exposed group declined at a slower rate following the AD program (DID = 0.73; 95% CI: 0.14, 1.31). The AD-exposed group had a 0.06 (95% CI: −0.11, −0.01) lower rate of mean monthly carisoprodol prescriptions compared to the control group following the AD program. There was no change in the rate of mean monthly non-BZD sedative-hypnotic prescriptions between the two groups. Conclusions: The higher relative rate of BZD prescribing in the AD-exposed group compared to the control group following the AD program may be reflective of an unintended consequence of opioid-focused AD programs as clinicians learn to be cautious about opioid prescribing. Our findings may suggest the need for incorporation of targeted education on appropriate BZD prescribing into opioid-focused AD programs as a featured component. These findings warrant further consideration and investigation before large-scale implementation of opioid-focused educational outreach programs.